Alkaline Earth Metal Complexes: Reactions of Calcium Ions with Common Plant Acids - Mahapatra (Chowdhury), Basabi; Bala, Shail; Kumar Mishra, Barun (Asian Journal of Chemistry, 2010)
The interaction of sodium salts of dicarboxylic acids and salicylic acid with bismuth(III) nitrate in non-aqueous solvent resulted in coordination complexes with the general composition Bi(NO3).LL.2 DMF (where LL is the bidentate ligand, namely oxalato, succinato, adipato, tartarato, phthalato and salicylato). Their physical characteristics and IR, UV spectra are reported. The nature of the metal-carboxyl group linkage is discussed.